Analisis Produksi Dan Kualitas Produk Dalam Meningkatkan Daya Saing Produk UMKM Permen Susu Sapi Khas Sumbawa : (Studi Pada Desa Penyaring Kecamataan Moyo Utara Kabupaten Sumbawa) - Dita Febrianti; Ramayanto; Abdul Hafiz (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
The UMKM specialty cow's milk candy was based on a milk innovation by the village PKK team in 1987. This UMKM has now become a home industry based on the employment criteria of 2-5 family members, located in the Filter Village, North Moyo District, Sumbawa Regency. This research aims to find out: 1) to find out what production factors are applied to increase the competitiveness of Sumbawa cow's milk candy UMKM. 2) to find out the quality of the products applied to increase the competitiveness of Sumbawa cow's milk candy UMKM. The research method uses qualitative research methods with a descriptive approach. Because this research aims to present research results based on facts in the field as they exist, related to production analysis and product quality in increasing the competitiveness of UMKM products typical Sumbawa cow's milk candy. The data collection techniques used by researchers are observation, interviews and documentation. The conclusion of the research results explains that: 1) the production factors applied are the first thing that is very important in increasing competitiveness because this is where milk candy products in the selection of raw materials used must be good because they can support good production. starting from choosing fresh milk that comes from farmers that is not mixed with water. 2) the product quality applied in increasing the competitiveness of Sumbawa's typical cow's milk candy has implemented product quality standards both in terms of distinctive taste, packaging, labels and durability of the product.